Fighting inflation with conventional and unconventional fiscal policy: The case for a new macroeconomic policy assignment - Peter Bofinger (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2024)
The study discusses the distribution of roles between monetary and fiscal policy in stabilising the price level. It questions the view that price level stabilisation should be the sole responsibility of central banks. It argues that there is a case for national governments also being responsible for price stability. The main results are the following: In the case of demand shocks, fiscal policy can react in a more timely and targeted manner than monetary policy. In the case of supply shocks, fiscal policy can shift the Phillips curve by varying indirect taxes, with price brakes and income policies. This is an advantage over monetary policy, which can only influence inflation indirectly by shifting the IS curve. In the recent energy crisis, the effects of this "unconventional fiscal policy" have been assessed quite positively. The case for a price stability mandate for national fiscal policy is particularly strong in the euro area. In the case of national supply and demand shocks in individual countries, the ECB can only provide an insufficient compensation, and its reaction has counterproductive effects in the rest of the monetary union. E.g., with a national price stability mandate, between 2014 and 2016, Germany would have been obliged to stimulate its economies, thereby supporting the ECB's fight against deflation.
Keywords: 330; Geldpolitik; Fiskalpolitik; unkonventionelle Fiskalpolitik; Europäische Zentralbank; Stabilitäts- und Wachstumspakt